HSK mới Cô đọng và súc tích HSK cấp độ 5 - Bảng câu hỏi, tài liệu nghe 新汉语水平考试 精讲精练 HSK四级 - Liang, Hong Yan Bian Zhu (Beijing Language and Cculture University Press, 2011)
Designed on the basis of the New HSK Chinese Proficiency Test Syllabus released by Hanban, this book includes 8 sets of simulated tests, listening materials, reference answers and problem-solving strategies, complying with the New HSK Syllabus in all aspe